Antifungal efficacy of Moringa oleifera leaf and seed extracts against Botrytis cinerea causing gray mold disease of tomato (Solanum lycopersicum L.) - Ahmadu,T. (2021)
Abstract Drawbacks associated with the use of chemical fungicides to control plant pathogenic fungi such as Botrytis cinerea stimulate the need for alternatives. Therefore, the present study was carried out to determine the antifungal potentials of Moringa oleifera extracts against B. cinerea. Phytochemical analysis using qualitative chemical tests revealed the presence of huge amount of crucial phytochemicals compounds like phenolic compounds, alkaloids and saponins in the M. oleifera leaf extract. Antifungal bioassay of the crude extracts indicated better mycelial growth inhibition by methanol leaf extract (99%). The minimum inhibitory concentration (MIC) was 5 mg/ml with 100% spore germination inhibition and minimum fungicidal concentration (MFC) was 10 mg/ml with 98.10% mycelial growth inhibition using broth micro dilution and poisoned food techniques. Gas chromatography–mass spectrometry (GC-MS) analysis led to the identification of 67 volatile chemical compounds in the leaf extract with 6-decenoic acid (Z)- (19.87%) was the predominant compound. Further chemical elucidation of the crude extracts performed by liquid chromatography with tandem mass spectrometry (LC-MS/MS) showed the presence of non-volatile chemical compounds, mostly flavones, flavonoids and phenolic acids (i.e. quercetin and kaempferol). Scanning electron microscopy and transmission electron microscopy analysis showed positive effect of M. oleifera leaf extract on the treated conidia and mycelium of B. cinerea. Findings revealed that irreversible surface and ultra-structural changes with severe detrimental effects on conidia and mycelium morphology compared to control treatment. Overall findings suggested that M. oleifera leaf extract is a promising candidate for biological control of fungal pathogens, thus limiting overdependence on chemical fungicides.